Milk Tumor Necrosis Factor Alpha and Interleukin-1Beta Among Toxoplasma gondii-Free and Infected Women (Baghdad Science Journal, 2022)
Pro-inflammatory cytokines play an important role in intercellular communications. In the last two decades, many cytokines have been identified in human milk. These cytokines are variable according to different conditions such as pathogenic infections which strongly stimulated the immune response. The present study aims to determine of IL1β and TNF-α in Toxoplasma gondii-free and infected women in an attempt to clarify the impacts of the infections on cytokines especially in mother's milk. The serum and milk sample were collected from 96 samples (48 for seropositive and 48 for seronegative). To confirm the Toxoplasma gondii infection; enzyme linked immunofluorescence assay (ELIFA) was used to detect anti-Toxoplasma IgG antibodies. TNF-α and IL1β levels were measured by ELISA technique. Regarding milk TNF-alpha, there were statistical differences in Toxoplasma-infected from Toxoplasma-free subjects, whereas no statistical variations in TNF-α were found between other studied groups. IL1β showed significant variation just between milk and serum in infected and non-infected subjects, whereas no variations were recorded in other groups. In conclusion, based on statistical analysis, present study showed good evidence that toxoplasmosis is one of the risk factors for increasing milk cytokine. Also, a significant increase in TNF-α and IL1β in mother's breast milk may indicate a key role for inducing or developing of inflammations in suckling. Thus, further investigations are needed to cover this area of study.